A SUPPORTING AND INHIBITING FACTORS OF SOCIAL INTERACTION OF SLOW LEARNER STUDENTS IN INCLUSIVE ELEMENTARY SCHOOL CLASSES: INCLUSIVE EDUCATION - Putri Fahmi; Liftiah Liftiah; Ali Formen (Universitas Muria Kudus, 2026)
This study aims to analyze the supporting and inhibiting factors of social interaction among slow learner students in inclusive elementary school classrooms. A qualitative approach with a case study design was employed. Data were collected at SDN 1 Sukorejo, SDN 2 Sukorejo, and SDN 3 Sukorejo, Tunjungan District, Blora Regency. Purposive sampling was applied to select informants consisting of slow learner students, inclusive classroom teachers, and parents. Three data collection techniques were used: participatory observation, in-depth semi-structured interviews, and documentation studies. Data were analyzed using Miles and Huberman's interactive analysis model comprising data reduction, data display, and conclusion drawing supported by source and technique triangulation as well as member checking. The results identified three supporting factors: (1) peer acceptance and empathy, especially informal peer tutoring behavior; (2) differentiated instructional strategies applied by teachers, such as mixed-ability grouping and think-pair-share techniques; and (3) active emotional support from parents at home. Three inhibiting factors were also identified: (1) social stigma and peer rejection that triggers social anxiety; (2) limited verbal communication skills and low self-efficacy of slow learner students; and (3) structural limitations, particularly the absence of a full-time Special Assistant Teacher (GPK) in all three schools. A comparative analysis across schools confirmed that social interaction quality among slow learner students is a multidimensional phenomenon shaped by the dynamic interplay of individual, teacher, classroom, family, and school policy factors.